2021
DOI: 10.3390/ph14101041
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Rich in Growth Factors in the Treatment of Endodontic Periapical Lesions in Adult Patients: A Narrative Review

Abstract: Platelet concentrates have been widely used in regenerative medicine, including endodontics. The aim of this manuscript was to assess critically the efficacy of PRF in the treatment of endodontic periapical lesions in adult patients on the basis of the literature. The PICO approach was used to properly develop literature search strategies. The PubMed database was analyzed with the keywords: “((PRP) OR (PRF) OR (PRGF) OR (CGF)) AND (endodontic) AND ((treatment) OR (therapy))”. After screening of 155 results, 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 141 publications
0
12
0
Order By: Relevance
“…TGF-b1 stimulates the expression of bone morphogenetic proteins and inhibits matrix metalloproteinases (MMPs) and other enzymes to stimulate osteoblast differentiation, while VEGF promotes angiogenesis, which occurs before bone formation, and is key to bone regeneration. A promising effect of sticky bone on longterm regeneration has also been anticipated (Zoltowska et al, 2021). An evaluation study showed that CGF can perform better as a scaffold when used in combination with Bio-Oss .…”
Section: Concentrated Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-b1 stimulates the expression of bone morphogenetic proteins and inhibits matrix metalloproteinases (MMPs) and other enzymes to stimulate osteoblast differentiation, while VEGF promotes angiogenesis, which occurs before bone formation, and is key to bone regeneration. A promising effect of sticky bone on longterm regeneration has also been anticipated (Zoltowska et al, 2021). An evaluation study showed that CGF can perform better as a scaffold when used in combination with Bio-Oss .…”
Section: Concentrated Growth Factorsmentioning
confidence: 99%
“…The growth factors and cytokines mentioned above stimulate osteoblast activity (Zoltowska et al, 2021). TGF-b1 stimulates the expression of bone morphogenetic proteins and inhibits matrix metalloproteinases (MMPs) and other enzymes to stimulate osteoblast differentiation, while VEGF promotes angiogenesis, which occurs before bone formation, and is key to bone regeneration.…”
Section: Concentrated Growth Factorsmentioning
confidence: 99%
“…If the RCT is unsuccessful or impracticable, apicoectomy should be recommended. In the case that both the RCT and apicoectomy are ineffective, a tooth extraction would be suggested [ 7 , 8 ]. There are supplementary procedures that may probably enhance periapical lesion healing, such as: using a triple antibiotic paste (Hoshino paste containing Ciprofloxacin 500 mg, Metronidazole 400 mg, and Minocycline 100 mg) as a canal dressing, photo-activated disinfection (PAD) or magnetostimulation.…”
Section: Introductionmentioning
confidence: 99%
“…There are four families of Platelet Rich Plasma concentrates: Pure Platelet Rich Plasma (P-PRP), Leukocyte and Platelet Rich Plasma (L-PRP), Pure Platelet Rich Fibrin (P-PRF) and Leukocyte and Platelet Rich Fibrin (L-PRF) [2], there are also 2 subcategories of L-PRF: Advanced Platelet Rich Fibrin (A-PRF) and Injectable Platelet Rich Fibrin (i-PRF) [4]. There is another platelet derived concentrate: Platelet Rich in Growth Factors (PRGF), developed by Anitua, et al (2015) by eliminating the white blood cells form PRP [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Concept of Regenerative endodontic procedures (REPs): Advanced-PRF (A-PRF), could be used in permanent teeth with closed apexes with periapical lesions, treated endodontically with the supplementation use of PRF. Although this procedure did reduce considerably the size of the periapical lesions, it is impossible to state how PRF affected the activity of the apical papilla stem cells and how these contributed to the healing of the periapical lesions 9, therefore it was not possible to assess the real effectiveness of PRF suplementation in this kind of REP [4,7].…”
mentioning
confidence: 99%